Archive, photography and the language of administration - Birkin, Jane, 1946- (Recursions: theories of media, materiality, and cultural techniques., 2021)
This alternative study of archive and photography brings many types of image assemblages into view, always in relation to the regulated systems operating within the institutional milieu. The archive catalogue is presented as a critical tool for mapping image time, and the language of image description is seen as having a life, a worth and an aesthetic value of its own. Functioning at the intersection of text and image, the book combines media culture, archival techniques, and contemporary discourse on art and conceptual writing.